Contesting conservation-planning: insights from Ireland - Parkinson, Arthur; Scott, Mark; Redmond, Declan (International Planning History Society Proceedings, 2016)
In most European countries, the 20th Century witnessed a growing interest in urban conservation as both a social movement and public policy domain, and by the 1960s urban conservation had emerged as a key planning and urban policy goal and a central feature of how cities positioned themselves within the globalised economy. However, where it evolves in contentious political contexts, urban conservation can be framed by competing priorities reflecting collective remembering, cultural politics and identities intertwined with the symbolic representation of the built environment. Ireland provides a unique lens to examine these themes in a western European context. Ireland is the only western European country to experience colonial domination. In relation to built heritage, Ireland’s urban centres have their historical roots in successive waves of colonial settlement, and buildings within these urban centres were inevitably perceived as tools of colonial oppression, representing the colonial state and power and domination of colonial capital interests. The built environment was also shaped by the tastes and preferences of the colonial elite, particularly in relation to prominent residences in the urban landscape, and outside of the main urban centres, landlord estates represented domination of landownership and agricultural production, manifested in large estate houses (referred to as the ‘big house’) and remodelled rural villages. This context provides an important backdrop to the evolution of conservation policy and practice in Ireland and to how representations of heritage have been continually (re)shaped in the urban development process. The aim of this paper is to chart the shifting representations of built heritage in Ireland, and their relevance in the emergence of conservation and heritage policy, set in the context of broader social, political and economic change over time. This is achieved, firstly, by a review of secondary source material to identify key events, eras and trends. Discourses of heritage are then examined in debates of the Oireachtas (the Irish legislature), which provide a consistent record of national heritage debates in the Irish state. This identifies tensions around the emergence of built heritage policy in a historic environment largely associated with colonial power and identity, and shifts in how the historic built environment was represented in different eras. These representations range from outright antipathy, towards a more positive revalorisation of heritage, and a recent awakening amongst policymakers to the potential of heritage as a driver of urban regeneration. We then relate these shifting discourses to policy evolution, particularly the late adoption of comprehensive legislative framework for conservation (in 1999) and the important influence of international charters rather than bottom-up or national priorities in policy agenda-setting. Finally, conclusions are developed to identify wider lessons from the production of urban conservation priorities in the context of contested heritage.